(untitled) - Burke, Joseph C. (San Francisco, 2005)
This astute book illuminates the inherent tension between accountability and autonomy. As Burke points out, the tension is healthy, but the union is essential. Educators and policymakers should use this book’s insights to achieve the goals that both share. The issue of higher education's accountability has never been more important. This book will be a valuable resource as we attempt to develop accountability systems to meet the challenges of today and, more importantly, those of tomorrow. It could not have come at a better time.
Keywords: Educational accountability,Education, Higher; Evaluation; United States,United States